Open abdomen in the management of complicated diaphragmatic hernia: a case report - Annicchiarico, Alfredo; Giuffrida, Mario; Del Rio, Paolo; Bonati, Elena; Perrone, Gennaro; Catena, Fausto (Acta Biomedica Atenei Parmensis, 2021)
Diaphragmatic hernia (DH) can be congenital or acquired. DH is a potentially life-threatening condition and the management in emergency setting remain unclear. Nonspecific symptoms can delay the diagnosis. We report a case of a 63-year-old man admitted for abdominal pain and nausea. He was successfully treated with damage control surgery.